Screening and evaluation of key technologies for non-bioartificial liver care: an empirical study - Yunzhi Zhang; Han Zhang; Ling Luo; Zhen Liu; Anlin Liu; Lin Shi; Lin Shi; Luwen Liang; Jing Zhao; Pu Chen; Yanli Yang (Frontiers in Medicine)
IntroductionTo identify key technologies within non-bioartificial liver (NBAL, an extracorporeal support system that temporarily replaces some of the liver’s functions) nursing to offer guidance for clinical practice. In the context of NBAL nursing, key technologies are crucial for successful implementation of artificial liver treatment, ensuring patient safety, and enhancing nursing quality. A review of both domestic and foreign literature revealed that studies on NBAL nursing technology are lacking and that the key technologies for NBAL nursing have not been clearly identified.MethodsUsing empirical research methods to collect and analyze data. First, the on-site survey method and literature research method were used to create a preliminary screening list of key technologies for NBAL care. Next, the focus group discussion method was used to establish the screening principles and evaluation indicators for these key technologies. Then, a two-round Delphi study via e-mail correspondence was used to screen and determine the key technologies for NBAL care. Finally, the analytic hierarchy process (AHP) and the technique for order preference by similarity to ideal solution (TOPSIS) comprehensive evaluation method were applied to evaluate these key technologies for NBAL care.ResultsSeventeen key technologies for NBAL care were identified. These include three basic nursing technologies, seven operating techniques, three items for treatment process monitoring technology, two items for health education, and two items for complication prevention and treatment technology.ConclusionThis study identified key NBAL nursing technologies, offering a systematic guide to enhance clinical practice. These technologies improve treatment safety, efficacy, and nursing standards, laying a foundation for NBAL care advancement.